Resistance Training Causes the Stretch-Induced Force Deficit-A Randomized Cross-Over Study - Konstantin Warneke; Katharina Turau; Lars Hubertus Lohmann; Martin Hillebrecht; David G. Behm; Andreas Konrad; Tobias Schmidt (MDPI AG, 2024)
Purpose: Stretch-induced force deficit suggests an acute stretch-specific strength capacity loss, which is commonly attributed to EMG reductions. Since those deficits could also be attributed to general fatigue induced by overloading the muscle, this study aimed to compare stretching with an exhausting calf raise programme to compare strength and stretching responses. Method: This study included 16 participants with different, high-duration calf muscle stretching effects (10, 20, 30 min of stretching) with resistance training (RT) (3 × 12 repetitions) performed until muscle failure, by using a cross-over study design with pre-post comparisons. Strength was tested via isometric plantar flexor diagnostics, while flexibility was assessed using the knee-to-wall test (KtW) and an isolated goniometer test. Results: Using a three-way ANOVA, RT strength decreases were greater compared to 10 and 20 min of stretching (p = 0.01-0.02), but similar to those of 30 min of stretching. ROM in the KtW showed no specific stretch-induced increases, while only the stretching conditions enhanced isolated tested ROM (p < 0.001-0.008). No RT-related isolated ROM increases were observed. Conclusions: The results showed both interventions had similar effects on strength and ROM in the calf muscles. More holistic explanatory approaches such as fatigue and warm-up are discussed in the manuscript and call for further research.